Perovskite La0.6Sr0.4CoO3-δ as a new polysulfide immobilizer for high-energy lithium-sulfur batteries. (October 2017) - Hao, Zhangxiang; Zeng, Rui; Yuan, Lixia; Bing, Qiming; Liu, Jingyao; Xiang, Jingwei; Huang, Yunhui
Abstract: To tackle the issue of low sulfur utilization and inferior cycle stability of sulfur cathode, we first report a new perovskite-type La0.6 Sr0.4 CoO3-δ (LSC) immobilizer to anchor the intermediate polysulfides via chemical interaction. The experimental results and theoretical calculations demonstrate that Sr doping results in valence variation in Co along with oxygen vacancy; The Co ions with mixed valence have strong adsorption to the polysulfide ions while the existence of oxygen vacancy enhances the binding strength between Li2 S4 and LSC. Based on LSC, a dual coxial LSC/S@C nanocable is successfully designed and fabricated. With a sulfur loading of 2.1 mg cm −2, the LSC/S@C cathodes demonstrate a high reversible capacity of 996 mA h g −1 at 0.5 C and an outstanding cycle stability with only 0.039% capacity fade per cycle over 400 cycles. Even with a high sulfur loading of 5.4 mg cm −2, the LSC/S@C cathode can still deliver similar sulfur utilization and excellent cycling stability. The excellent cycle stability benefits from the chemical interaction between LSC and polysulfides, and the physical entrapment of the carbon shell. Moreover, the highly conductive LSC@C host and the porous interconnected fiber web-like architecture facilitate the mass transfer during charge/discharge process synchronously. Graphical abstract: Highlights: A novel perovskite La0.6 Sr0.4 CoO3-δ (LSC) immobilizer is firstly introduced into the Li-S system. A dual core-shell structure of LSC/S@C cathode have successfully designed and fabricated. The chemical bond between LSC and polysulfide is confirmed by the DFT calculation, XPS spectra and iodometric titrations. With a high sulfur loading of 5.4 mg cm −2, the LSC/S@C cathode deliver comparable cycling stability.